Dweck’s Growth Mindset Theory in Health Professions Education: A Bibliometric Review - Kelsey D. Frederick; Lisa S. Lewis; Suzanne Larson; Janet Cooley; Anita J. Cleven; Stephanie Dawson; Elizabeth R. Blackwood; Cheryl A. Williams (Medical Science Educator, 2026)
Abstract Carol Dweck’s Growth Mindset Theory (GMT) has gained increasing attention in health professions education (HPE), yet its development has not been comprehensively mapped. This first bibliometric review analyzed 142 HPE articles identified through a Scopus search and Bibliometrix analysis. Publications increased substantially after 2016, with rapid growth following 2020. Commonly associated concepts included resilience, competency-based education, motivation, and self-regulation. The United States produced the most publications and citations, and medicine, nursing, and pharmacy were the most represented professions. Although GMT scholarship in HPE is expanding, greater collaboration and more robust research designs are needed to strengthen the evidence base.